A Critical Analysis of the Evolving gender Perspective in Contemporary Dimensions: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
It is essential that the obvious conduct attributed to a third party be confirmed beyond areasonable doubt in cases where such allegations are made. These family members cannot be heldcriminally liable for dowry-related fatalities on the basis of inferences and assumptions alone. However, inrecent years, there has been a growing tendency to accuse both sets of in-laws of a deceased couple indowry death cases, which might undermine the prosecution's case even if the real perpetrators areidentified. In their zeal and desperation to seek conviction for the greatest number of people, the parentsof the deceased have been found to be attempting to include the relatives, eventually weakening thecase of prosecution even against the true accused, as appears to have occurred in the instant case.While protecting women from abuse is the primary focus of S.498-A, other members of the family, suchas minors and the elderly, must be taken into account. In order to strike a fair balance betweencompeting interests in the home, it has become clear that the current cruelty laws must be revised.Originally, the law was enacted to save defenseless wives from their rapacious partners and theirfamilies, but times have changed.